Influence of chemical composition on the elastic properties of phosphate glass / Azman, K. … [et al.] - K., Azman,; H.A.A., Sidek,; H., Azhan,; M., Suhaimi,; J., Nazrah, (2002)
This paper will report the influence of the chemical composition that affected the mechanical properties of phosphate glass. In this study lead oxide (PbO) has been used as the chemical reagent and the elastic property was evaluated by using the ultrasonic measurement technique. A series of phosphate-based glass with the percentages of lead oxide varies from 10% to 60% were prepared. An ordinary melt-quench technique of preparation produced high quality of lead phosphate glasses (PbO-P2O5). The ultrasonic measurement was carried out for the glass series at room temperature by using the Matec MBS 8000 Instruments. From the velocities of the ultrasonic waves namely longitudinal, VL and shear, Vs waves the data has been used to estimate the elastic modulus such as bulk modulus. Young's modulus, Poisson ratio etc. for each composition.